(untitled) (Modern education and development, 2025)
This article discusses the role of medicinal plants in increasing students’ interest in biology. At the same time, it highlights the idea of ​​cultivating qualities such as responsibility for nature conservation and a sense of responsibility for nature conservation in students through the cultivation of medicinal plants in an educational experimental plot.